2013
DOI: 10.1161/circresaha.113.301546
|View full text |Cite
|
Sign up to set email alerts
|

Gli3 Regulation of Myogenesis Is Necessary for Ischemia-Induced Angiogenesis

Abstract: Rationale A better understanding of the mechanism underlying skeletal muscle repair is required to develop therapies that promote tissue regeneration in adults. Hedgehog signaling has been shown previously to be involved in myogenesis and angiogenesis: 2 crucial processes for muscle development and regeneration. Objective The objective of this study was to identify the role of the hedgehog transcription factor Gli3 in the crosstalk between angiogenesis and myogenesis in adults. Methods and Results Using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…The mechanism is rapid and independent of Gli-dependent transcription. Remarkably, this study and a previous one also showed evidences of activation of G 12 by Smo [152,153]. Altogether, numerous evidences demonstrate that Smo does couple to heterotrimeric G proteins of the G i family.…”
Section: Regulation Of Calcium Levelssupporting
confidence: 86%
“…The mechanism is rapid and independent of Gli-dependent transcription. Remarkably, this study and a previous one also showed evidences of activation of G 12 by Smo [152,153]. Altogether, numerous evidences demonstrate that Smo does couple to heterotrimeric G proteins of the G i family.…”
Section: Regulation Of Calcium Levelssupporting
confidence: 86%
“…As we move toward this goal, a large body of ongoing tissue-engineering work revolves around establishing perfusable capillary networks in vitro and inducing the ingrowth of functional vasculature in vivo (114, 187). Additionally, complex bidirectional interactions between myogenic and vascular cells are increasingly recognized as being critical for muscle function, disease, and regeneration (188190). As such, the ability to engineer 3D skeletal muscle tissues with native-like architecture, mature contractile function, and a vascular bed—feats not yet accomplished—would promote both basic studies of muscle biology and the development of improved cell- and material-based therapies for VML.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates that therapies capable of coordinately improving local skeletal muscle angiogenesis and myogenesis have a better impact on tissue regeneration during hindlimb ischemia in rodents (61, 62). However, dissecting the contribution of specific population of cells located at the skeletal muscle microenvironment to PAD establishment and/or progression remains a challenge.…”
Section: Skeletal Muscle Microenvironmentmentioning
confidence: 99%